MOTIVATION OF IT-PROFESSIONALS. CREATION OF A MOTIVATIONAL ENVIRONMENT FROM SCHOOL UNTIL THE END OF CAREER - Zavileysky, M.C. (Journal of Information Technologies in Education (ITE), 2010)
Some of the major factors influencing the motivation of IT-professionals are connected with the most important attributes of their educational environment. How to respect autonomy, provide access for diversified opportunities, support heterogenic teams of peers? Some ideas relating to the creation of a motivational environment and how the role of teachers can be transformed are discussed.